Development of Foot Massage Program on Nausea and Vomiting for Cancer Patients: A Literature Review - Prapti, Ni Ketut Guru; Petpichetchian, Wongchan; Chongcharoen, Wimonrat (Nurse Media Journal of Nursing, 2012)
Objective: This study aims to develop a foot massage program to support care activity in reducing nausea and vomiting for cancer patients undergoing chemotherapy. Two phases, a literature review and the development of a foot massage program were conducted. The literature review was to analyze state of the art massage techniques by reviewing problems, related theories and supporting evidence. Method: Eight published studies in the English language were reviewed. A massage can be performed for different durations, from 10 minutes up to 60 minutes for three to six weeks and can be applied on various body areas. We found that the soft stroke/effleurage seems to be the best method and is most suitable for patients with cancer. It is also evident that foot massaging can be applied as a modality to reduce nausea and vomiting for cancer patients undergoing chemotherapy. Result: We developed a foot massage program specifically for patients with cancer. The foot massage program comprised of three sessions, including 1) education session, 2) preparation session, and 3) foot massage session. In the education session, patients obtain brief information about the definition of a foot massage, the benefits and contraindication of foot massaging. During the preparation phase, foot soaking and warming up are performed. Subsequently, the foot massage is applied and should last for 30 minutes. Further research is recommended to test the effectiveness of the proposed foot massage program for nausea and vomiting in cancer patients across countries including Indonesia. Key Words: Foot massage program, chemotherapy, nausea and vomiting